2021
DOI: 10.37301/jmubh.v16i2.19025
|View full text |Cite
|
Sign up to set email alerts
|

Menganalisis Efektivitas Ewom Pada Customer Purchase Intention Dengan Menggunakan Social Networking of Smartphone in Batam

Abstract: Social Networking is used by a lot people in this world so they still can connected with their families, friend and customer. Some people used to tell their families or friend what’s their dailies do by putting a picture selfie. The most important part where there’s a people use Social Networking as business purpose like make adversiting for their business without use any capital.The purpose of the study was investigated how far the effect of electric Word Of Mouth (eWOM) inside social networking sites (facebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…02, July, 2023ISSN : 1907 Moreover, research conducted in the field of tourism also revealed the same thing that the joint value formation by consumers towards a tourist destination has a positive influence on consumers to have a desire in visiting a destination (Xu, Tan, Lu, Li, & Qin, 2021). Electronic word of mouth (e-WOM) research demonstrates that customer behavior on social networking sites and shared value creation will assist marketers in creating new methods for disseminating information about their products on networking sites (Hasan & Lim, 2021). Thus, the perceived value co-creation in social media marketing is also able to encourage consumer intentions to invest.…”
Section: Resultsmentioning
confidence: 99%
“…02, July, 2023ISSN : 1907 Moreover, research conducted in the field of tourism also revealed the same thing that the joint value formation by consumers towards a tourist destination has a positive influence on consumers to have a desire in visiting a destination (Xu, Tan, Lu, Li, & Qin, 2021). Electronic word of mouth (e-WOM) research demonstrates that customer behavior on social networking sites and shared value creation will assist marketers in creating new methods for disseminating information about their products on networking sites (Hasan & Lim, 2021). Thus, the perceived value co-creation in social media marketing is also able to encourage consumer intentions to invest.…”
Section: Resultsmentioning
confidence: 99%